Diseño de un restaurante de comidas típicas amazónicas “ALLY MICUNA”, mediante la elaboración del plan de negocios para rescatar la gastronomía en la Parroquia Pano, Cantón Tena, Provincia de Napo - Viteri Andi, Alexandra Karina (2018)
The work was carried out in the Pano parish, seeing the need of the villagers not having an infrastructure of a company dedicated to the service of food that allows to create some sources of work, to take advantage of the existing natural resources and agricultural products of the zone, creating an economic value. For this reason, it has been necessary to determine the general objective: "Elaborate a business plan for the Restaurant of typical Amazonian foods" Ally Micuna "in Pano Parish, Canton Tena, and province of Napo", which will contribute to the development economic and promote the gastronomic tourism, which will serve as a guide for the correct functioning of the restaurant. For the fulfillment of the research work methods were used as: inductive, deductive, descriptive and analytical; techniques such as: the survey, interview, direct observation and bibliographic. As for the results, it was evident in the research analysis that the following objectives were determined for the project: the first objective was focused on an in-depth analysis of the tourist gastronomy. The second objective determined the market study where the supply and demand were analyzed. Distribution channels, product strategy and marketing were applied. The third objective was used the Technical Study which includes the physical distribution of the restaurant (flat), the size and location of the project, and the Administrative study. The fourth objective was to invest $ $75.253, 61 to start up the business. In the fifth objective, positive indicators were obtained, with the following indicators: (V.A.N.) $; 564.611,29; determines that, the project is viable and with a (T.I.R) 113.65% since the investment will be recoverable in 1 year and 6 months demonstrating that the project is feasible, whose conclusions and recommendations so determine, attaching the bibliography consulted with their respective annexes.